Indications of Tonsillectomy and Adenoidectomy in Dr. Hasan Sadikin General Hospital Bandung - Atiyah, Dini; Permana, Agung Dinasti; Hartanto, Rudy (Althea Medical Journal, 2015)
Â Â Background: Tonsillectomy is the intervention to take out the palatine tonsils either whole or sub capsular, while adenoidectomy is the intervention of extraction of the adenoid gland which is commonly done with curettage method. Both interventions are done to eliminate repeated infections and also obstructions due to inflammation and hypertrophy of the tonsils and adenoids. This study was conducted to examine the indications of tonsillectomy and adenoidectomy in the Departement of Otorhinolaryngology and Head Neck Surgery Dr. Hasan Sadikin General Hospital Bandung in the period of January 2009âDecember 2011. Methods: A cross-sectional descriptive study was conducted in OctoberâNovember of 2012 using 207 medical records of patients who had tonsillectomy and adenoidectomy executed in the Department of Otorhinolaryngology and Head Neck Surgery Dr. Hasan Sadikin General Hospital, Bandung in the period of January 2009âDecember 2011. Data collected were age, gender, main complaint, tonsil size, history of repeated infections, history of snoring as well as of Obstructive Sleep Apnea Syndrome (OSAS). The indication for tonsillectomy and adenoidectomy such as infection, obstruction and neoplasia was selected.Results: The indications of tonsillectomy and adenoidectomy were infection at 106 (51.2%) patients, obstruction at 100 (48.3%) patients, and neoplasia at 1 (0.05%) patient.Conclusions: The most numerous indications for tonsillectomy and tonsilloadenoidectomy in the Department of Otorhinolaryngology and Head Neck Surgery Dr. Hasan Sadikin General Hospital were infection.Keywords: Adenoid, adenoidectomy, indication, tonsil, tonsillectomy DOI: 10.15850/amj.v2n1.447Â